Chitosan / poly (p-dioxanone) composite hydrogel as well as preparation method and application thereof
By combining chitosan with polyptioxane and forming a composite hydrogel with network interpenetrating structure through freeze-thawing treatment, the shortcomings of chitosan porous gel scaffolds in terms of mechanical strength and biodegradability are solved, and the improvement of mechanical properties and biocompatibility are achieved.
Patent Information
- Application Number
- CN202411839910.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing chitosan porous gel scaffolds have shortcomings in mechanical strength, cell-specific binding sites, structural stability and biodegradability, which limits their application in tissue engineering.
By combining chitosan with a deacetylation degree of ≥95% with polyptioxane with a viscosity average molecular weight of 1×104 to 1×106, a crosslinked polymer swelling liquid was formed, and a composite hydrogel with a network interpenetrating structure was prepared by repeated freeze-thawing treatments.
It significantly improves the mechanical strength of chitosan hydrogel, including tensile and compression properties, while maintaining good biocompatibility and degradability, reducing damage and side effects to human organs.
Smart Images

Figure CN119661907A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tissue engineering, and in particular to a chitosan / polydioxanone composite hydrogel and a preparation method and application thereof. Background Art
[0002] The material used as a tissue engineering scaffold must have an interconnected and porous pore structure to facilitate cell attachment, proliferation and differentiation, so as to facilitate tissue growth and functional recovery, and provide channels for the transport of nutrients and the discharge of metabolic waste. Tissue engineering scaffolds should have sufficient mechanical strength to provide support for tissue regeneration at the implantation site; tissue engineering scaffolds must also have good biocompatibility, suitable biodegradability, non-toxicity, and the characteristics of promoting good integration with the tissues around the implantation site. Studies have shown that chitosan is one of the ideal materials in the field of tissue engineering scaffolds. Compared with traditional surgical methods, chitosan gel treats or repairs defective tissues in a minimally invasive manner, and can also control tissue induction factors through chemical modification; in addition, chitosan hydrogel also has structural characteristics similar to the extracellular matrix of the human body, which can transport and store cells.
[0003] Based on this, the use of chitosan to form porous gel scaffolds is a research and development direction in the field of tissue engineering scaffolds; however, porous gel scaffolds formed by chitosan have some shortcomings, such as: the mechanical strength of chitosan scaffolds is weak, lack of cell-specific binding sites, the scaffold structure is easily destroyed in the physiological environment, and the chitosan hydrogel has low in vivo degradability, which seriously limits its application in tissue engineering. Therefore, researchers have combined chitosan with synthetic polymers or natural biopolymers to improve the mechanical strength and biological activity of gel scaffold materials in a complementary manner, providing the required mechanical support for tissue regeneration.
[0004] At present, there are many chitosan bioengineering scaffolds on the market. The published patent CN105944150A discloses a chitosan / collagen hydrogel, which can obtain a biomimetic structure similar to natural bones by adding collagen to chitosan, increase the production of calcium and sulfate glycosaminoglycans, and has the potential for osteogenesis and cartilage formation, so that the mechanical properties of chitosan / collagen gel materials are improved; however, the presence of collagen in the body increases the risk of immune rejection in the human body. The published patent CN113929819A discloses a chitosan / polyacrylamide hydrogel, which uses chitosan as the main body and polyacrylamide hydrogel as a porous skeleton to prepare a porous composite hydrogel with good mechanical properties, that is, the overall mechanical strength is provided by the polyacrylamide porous skeleton; however, acrylamide has certain neurotoxicity, shows carcinogenic potential in animal studies, and long-term existence increases health risks, so this hydrogel material is generally used for adsorption materials. In addition, there is a commonly used polyvinyl alcohol-based composite hydrogel. Although this hydrogel has many advantages in performance, polyvinyl alcohol may cause skin irritation and stinging when used in the human body for a long time, and may even cause allergic reactions in some people.
[0005] Therefore, in order to solve the above problems, it is necessary to further develop and modify the porous gel formed by chitosan, so as to ensure that the mechanical strength and flexibility of the hydrogel are improved while making it have good biocompatibility and complete degradability, and effectively avoid health risks such as antigen rejection. Summary of the invention
[0006] The purpose of the present invention is to provide a chitosan / polydioxanone hydrogel having both good mechanical strength and good biological properties.
[0007] Another object of the present invention is to provide a method for preparing the chitosan / polydioxanone hydrogel.
[0008] Another object of the present invention is to provide an application of the chitosan / polydioxanone hydrogel.
[0009] To this end, the technical solution of the present invention is as follows:
[0010] A chitosan / polydioxanone composite hydrogel, which is composed of chitosan with a deacetylation degree of ≥95% and a polydioxanone with a viscosity average molecular weight of 1×10 4 ~1×10 6 The cross-linked polymer swelling liquid formed by polydioxanone is prepared by repeated freeze-thaw treatment; wherein the amount of polydioxanone is 1wt% to 18wt% of the weight of chitosan, and more preferably 3.5wt% to 12wt%.
[0011] The chitosan / polydioxanone composite hydrogel uses chitosan as a main material and polydioxanone as a reinforcing material. The polydioxanone is dispersed in chitosan for a cross-linking reaction, and a physical freeze-thaw method is used to introduce polydioxanone molecular chains having excellent flexibility and mechanical properties into the chitosan hydrogel with a network structure, thereby forming a hydrogel with a network interpenetrating structure, thereby modifying the chitosan hydrogel, in order to obtain a.
[0012] It should be noted that, in the process of selecting the main material, the applicant has tried to use sodium alginate and gelatin, which are also biocompatible and degradable, in addition to chitosan. However, in the process of preparing hydrogel, although sodium alginate also has good biocompatibility, water absorption and moisture retention, and is widely available, safe and non-toxic, and degradable; but its gel controllability is poor and its mechanical strength is low, which poses great difficulties in the preparation process; and although gelatin also has good bioaffinity and degradability, the uncross-linked gelatin film has the disadvantages of being easily soluble in water, hard and brittle, and having poor mechanical properties; therefore, chitosan was finally used as the material for preparing the gel main body.
[0013] A method for preparing the chitosan / polydioxanone composite hydrogel comprises the following steps:
[0014] S1, dissolving chitosan in an acidic aqueous solution to prepare a chitosan solution;
[0015] S2, dissolving the cross-linking agent in the chitosan solution to obtain a chitosan solution containing the cross-linking agent;
[0016] S3, dissolving polydioxanone in an organic solvent to prepare a PPDO solution;
[0017] S4. Slowly add the PPDO solution to the chitosan solution containing the crosslinking agent, and keep it at a constant temperature of 55°C to 60°C and stir for 1 hour to mix the two evenly; continue stirring for 3 hours to 6 hours to allow the chitosan to fully hydrate and swell; then cool to room temperature to obtain a CS / PPDO swelling solution;
[0018] S5, repeatedly freeze-thaw the CS / PPDO swelling solution to obtain a freeze-thawed CS / PPDO hydrogel;
[0019] S6. The freeze-thawed CS / PPDO hydrogel is freeze-dried and then placed in deionized water to fully absorb water and swell, thereby obtaining a CS / PPDO composite hydrogel with swelling equilibrium and free of organic solvent.
[0020] In step S1 , the acidic aqueous solution is an acetic acid aqueous solution, a formic acid aqueous solution, an oxalic acid aqueous solution or a carbonic acid aqueous solution with a pH of 3-6, preferably an acetic acid aqueous solution with a pH of 3-6.
[0021] In step S1, the amount of the acidic aqueous solution is preferably 20 to 25 times the weight of the chitosan.
[0022] In step S1, the preparation temperature of the chitosan solution is 45°C to 60°C, preferably 55°C.
[0023] In step S2, the cross-linking agent is sodium citrate, calcium chloride or glutaraldehyde, preferably sodium citrate; the amount of the cross-linking agent is preferably 0.25 to 0.3 times the weight of chitosan.
[0024] In step S3, the organic solvent is dimethyl sulfoxide, N-dimethylformamide or chloroform, preferably dimethyl sulfoxide. The amount of the organic solvent used is determined by the amount of the organic solvent that can dissolve the polydioxanone.
[0025] In step S3, the preparation temperature of the PPDO solution is preferably 60°C to 80°C, preferably 75°C.
[0026] Preferably, before performing step S5, the CS / PPDO swelling solution is defoamed at room temperature to obtain a uniform CS / PPDO swelling solution.
[0027] The defoaming treatment method may be, but is not limited to, an ultrasonic defoaming method, a vacuum defoaming method or a room temperature static method. The ultrasonic defoaming method is: placing the bubbles in the CS / PPDO swelling solution in an ultrasonic cleaning machine, and ultrasonicating for 10 minutes to 30 minutes to remove the bubbles; the vacuum defoaming method is: placing the bubbles in the CS / PPDO swelling solution in a vacuum oven, the pressure of which is 0 to -0.1 MPa, and the treatment time is 10 minutes to 30 minutes; the room temperature static method is: standing at room temperature for 2 hours to 4 hours.
[0028] Preferably, in step S5, the method of repeated freeze-thaw treatment is: freezing the CS / PPDO swelling solution at -48°C to -12°C for 8h to 12h, and then returning it to room temperature for 3h to 6h; repeating the above freeze-thaw operation 4 to 6 times to obtain a frozen-thawed CS / PPDO hydrogel.
[0029] Preferably, in step S6, the temperature of the freeze-drying treatment is -60°C to -40°C, the pressure is 0.4 mbar to 0.01 mbar, and the freeze-drying time is 24h to 48h.
[0030] Preferably, in step S6, the water absorption and swelling method is: placing the freeze-dried CS / PPDO hydrogel in deionized water to absorb and swell for 12 h to 24 h, so that the hydrogel fully absorbs water.
[0031] An application of the chitosan / polydioxanone composite hydrogel as claimed in claim 1 for skin tissue engineering, soft tissue engineering and bone tissue engineering.
[0032] Compared with the prior art, the chitosan / polydioxanone composite hydrogel is effective in that: on the one hand, the chitosan / polydioxanone hydrogel uses chitosan as the main material and polydioxanone as the reinforcing material, and polydioxanone is dispersed in the chitosan hydrogel containing a cross-linking agent, and a physical freeze-thaw method is used to introduce the polydioxanone molecular chain with excellent flexibility and mechanical properties into the chitosan hydrogel with a network structure, thereby forming a hydrogel with a network interpenetrating structure; the hydrogel structure greatly improves the mechanical strength of the chitosan hydrogel, and greatly improves its mechanical properties, including tensile properties and compression properties. On the other hand, chitosan and polydioxanone both have good degradability and biocompatibility, and their decomposition products are harmless to the human body, and greatly reduce the damage and side effects to human organs, showing good biocompatibility; and, due to the network interpenetrating structure characteristics of the hydrogel, it has a porous structure. The biological properties of the two can also make it more conducive to the adhesion and growth of cells when applied to tissue engineering, so that it has broad application prospects in the biomedical field; in addition, the preparation method of the chitosan / polydioxanone hydrogel is simple and the conditions are easy to control, so it has broad application prospects in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] FIG. 1( a ) is a photograph of a columnar sample of chitosan / polydioxanone hydrogel prepared in Example 1, Example 2 and Example 3 of the present invention placed in a sample bottle;
[0034] FIG1( b ) is a photograph of a sheet sample of the chitosan / polydioxanone hydrogel prepared in Example 1 of the present invention;
[0035] Figure 2 This is a comparison diagram of infrared spectra of the CS / PPDO hydrogel prepared in Example 3 of the present invention and the chitosan hydrogel prepared in Comparative Example 1;
[0036] Figure 3 This is a scanning electron micrograph of the brittle fracture surface of the chitosan / polydioxanone hydrogel prepared in Example 3 of the present invention;
[0037] Figure 4 A comparison graph of mechanical tensile test result curves of chitosan / polydioxanone hydrogels prepared in Examples 1, 3, 6 and 7 of the present invention and chitosan hydrogel prepared in Comparative Example 1;
[0038] Figure 5 A bar chart comparing the water absorption and swelling test results of the chitosan / polydioxanone hydrogels prepared in Examples 3, 6 and 7 of the present invention and the chitosan hydrogel of Comparative Example 1 in deionized water;
[0039] Figure 6 It is a line chart comparing the mass loss of the chitosan / polydioxanone hydrogel prepared in Example 3 of the present invention and the chitosan hydrogel prepared in Comparative Example 1 after seven weeks of simulated degradation experiment in phosphate buffer. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.
[0041] Example 1
[0042] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0043] S1. Add 0.85 g of chitosan (CS) to 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and place the mixture in a constant temperature oil bath at 55° C. and stir to dissolve to obtain a chitosan solution; wherein the chitosan is produced by Shanghai Aladdin Biochemical Technology Co., Ltd., and has a deacetylation degree of ≥95% and a viscosity of 100 mpa.s to 200 mpa.s, and the following Examples 2 to 7 are the same;
[0044] S2, adding 0.25 g of sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution containing sodium citrate;
[0045] S3, 0.01g viscosity average molecular weight 5×10 5 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide aqueous solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0046] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 55°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0047] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -24°C for 12 hours and returned to room temperature for thawing for 6 hours; the above freezing-thawing operation was repeated 5 times to obtain a CS / PPDO hydrogel;
[0048] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -40°C and 0.1 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0049] Example 2
[0050] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0051] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0052] S2, adding 0.255 g of calcium chloride to the chitosan solution, and continuing to stir and dissolve in a 60° C. constant temperature oil bath to obtain a chitosan solution containing calcium chloride;
[0053] S3, 0.03g viscosity average molecular weight 1.0×10 4 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0054] S4. Slowly add the PPDO solution to the chitosan solution containing calcium chloride, and place it in a 60°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 5 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0055] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -48°C for 8 hours, and then returned to room temperature for 3 hours to thaw; the above freezing-thawing operation was repeated 4 times to obtain a CS / PPDO hydrogel;
[0056] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -60°C and 0.4 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel that does not contain organic solvents.
[0057] Example 3
[0058] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0059] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0060] S2, adding 0.25g sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0061] S3, 0.05g viscosity average molecular weight 5.0×10 5 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0062] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 55°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0063] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -24°C for 12 hours, and then returned to room temperature for thawing for 6 hours; the above freezing-thawing operation was repeated 5 times to obtain a CS / PPDO hydrogel;
[0064] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -40°C and 0.1 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0065] Example 4
[0066] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0067] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0068] S2, adding 0.213 g of sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 45°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0069] S3, 0.07g of viscosity average molecular weight 1.0×10 6 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 80° C. to obtain a PPDO solution;
[0070] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 60°C constant temperature oil bath and continue stirring for 2 hours to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0071] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -36°C for 10 hours, and then returned to room temperature for thawing for 5 hours; the above freezing-thawing operation was repeated 4 times to obtain a CS / PPDO hydrogel;
[0072] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 48 hours at -45°C and 0.05 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 24 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0073] Example 5
[0074] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0075] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0076] S2, adding 0.25g sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0077] S3, 0.09g of viscosity average molecular weight 5.0×10 5 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0078] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 55°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0079] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -24°C for 12 hours, and then returned to room temperature for thawing for 6 hours; the above freezing-thawing operation was repeated 5 times to obtain a CS / PPDO hydrogel;
[0080] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -40°C and 0.1 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0081] Example 6
[0082] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0083] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0084] S2, adding 0.25g sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0085] S3, 0.10g of viscosity average molecular weight 5.0×10 5 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0086] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 55°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0087] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -24°C for 12 hours, and then returned to room temperature for thawing for 6 hours; the above freezing-thawing operation was repeated 5 times to obtain a CS / PPDO hydrogel;
[0088] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -40°C and 0.1 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0089] Example 7
[0090] A chitosan / polydioxanone composite hydrogel is prepared by the following method:
[0091] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0092] S2, adding 0.25g sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0093] S3, 0.15g of viscosity average molecular weight 5.0×10 5 Add polydioxanone (PPDO) into 20 mL of dimethyl sulfoxide solution, stir and dissolve at 75°C to obtain a PPDO solution;
[0094] S4. Slowly add the PPDO solution to the chitosan solution containing sodium citrate, and place it in a 55°C constant temperature oil bath and continue stirring for 1 hour to mix evenly, and then stir for another 6 hours to allow the chitosan to fully hydrate and swell, and then cool to room temperature to obtain a CS / PPDO swelling solution;
[0095] S5. At room temperature, the CS / PPDO swelling solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform CS / PPDO swelling solution; the uniform CS / PPDO swelling solution was then frozen at -24°C for 12 hours, and then returned to room temperature for thawing for 6 hours; the above freezing-thawing operation was repeated 5 times to obtain a CS / PPDO hydrogel;
[0096] S6. Place the hydrogel after freeze-thawing in step S5 into a freeze dryer and freeze-dry for 24 hours at -40°C and 0.1 mbar to completely dry the hydrogel, thereby removing organic solvents such as acetic acid and dimethyl sulfoxide in the hydrogel and further enhancing the mechanical strength of the hydrogel by freeze-thawing; take out the gel and place it in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium and produce a CS / PPDO composite hydrogel free of organic solvents.
[0097] Comparative Example 1
[0098] A chitosan hydrogel is prepared by the following method:
[0099] S1. Add 0.85 g of chitosan (CS) into 20 mL of a mixed solution prepared by acetic acid and water in a weight ratio of 1:1, and stir and dissolve in a constant temperature oil bath at 55° C. to obtain a chitosan solution;
[0100] S2, adding 0.25g sodium citrate to the chitosan solution, and continuing to stir and dissolve in a 55°C constant temperature oil bath to obtain a chitosan solution with sodium citrate crosslinking agent;
[0101] S3, adding 20 mL of dimethyl sulfoxide aqueous solution to the chitosan solution, and stirring at 55°C for 6 h to allow the chitosan to fully hydrate and swell;
[0102] S4. At room temperature, the chitosan solution was placed in an ultrasonic cleaning machine and ultrasonicated for 30 minutes to remove bubbles to obtain a uniform chitosan swelling solution; the uniform chitosan swelling solution was frozen at -24°C for 12 hours, and then returned to room temperature for thawing for 6 hours; the freezing-thawing operation was repeated 5 times to obtain a chitosan hydrogel;
[0103] S5. The hydrogel after freeze-thawing in step S5 is placed in a freeze dryer, freeze-dried at -40°C and 0.1 mbar for 24 hours, and then placed in deionized water to fully absorb water for 12 hours to achieve swelling equilibrium, thereby obtaining a CS hydrogel without organic solvent.
[0104] Comparative Example 2
[0105] A chitosan / polydioxanone composite hydrogel, the preparation method of which is substantially the same as that of Example 1, except that: the chitosan in step S1 is chitosan with a deacetylation degree of ≈65%.
[0106] Performance Test:
[0107] (I) Macro- and microstructural characterization of chitosan / polydioxanone hydrogels:
[0108] 1. Macrostructure characterization:
[0109] As shown in Figure 1 (a), the chitosan / polydioxanone hydrogel prepared in Example 1, Example 2 and Example 3 is placed in a sample bottle. It can be seen from the figure that the hydrogels prepared in Examples 1-3 are slightly yellow and transparent. The three are placed in an inverted state in three sample bottles, and do not show a flowing state, which proves that the hydrogel preparation is successful. Similarly, the chitosan / polydioxanone hydrogels prepared in Examples 4-7 also have the same performance state performance.
[0110] As shown in Figure 1(b), the chitosan / polydioxanone hydrogel swelling liquid prepared in Example 1 is placed in the sample plate slot, and then a photo of the sheet sample is obtained after repeated freeze-thaw, freeze-drying, and swelling. It can be seen from the figure that when the two ends of the sheet sample are held by both hands and stretched, the sheet sample is obviously not easily broken and has certain tensile properties.
[0111] 2. Microstructure characterization:
[0112] The chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 were subjected to infrared testing to verify whether the PPDO long chains were successfully introduced into the CS / PPDO hydrogel structure. Figure 2 The infrared spectra of the CS / PPDO hydrogel prepared in Example 3 and the chitosan hydrogel prepared in Comparative Example 1 are shown. -1 The left and right are carbonyl C=O stretching vibration absorption peaks; 3251cm in the structure of chitosan -1 The broad peaks on the left and right are the overlapping peaks of NH and OH; -1 The nearby peaks can represent OH functional groups; and the wave number 1715cm -1 It is usually related to the stretching vibration of carbonyl (C=O). The composite hydrogel has a wavelength of 1715 cm -1 The peak at 1715 cm is obviously higher, and PPDO mainly contains carbonyl (C=O), which indicates that PPDO is successfully added into CS / PPDO hydrogel as a reinforcing material. -1 The left and right are carbonyl C=O stretching vibration absorption peaks. Similarly, the infrared spectra of other examples also have the same characterization results as above.
[0113] The brittle fracture surfaces of the chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 were scanned by electron microscope to determine their microstructural characteristics. Figure 3The figure shows a scanning electron microscope image of the brittle section of the CS / PPDO hydrogel prepared in Example 3; it can be seen from the figure that the microstructure of the CS / PPDO hydrogel prepared in Example 3 does have a continuous network interpenetrating structure, and uniformly distributed micron pores can be clearly observed on the brittle section, with a pore range of 1um to 8um; the void structure of the hydrogel is not only conducive to the growth and adhesion of cells, but also conducive to the absorption of tissue fluid by the hydrogel, providing an excellent environment for cell growth. Similarly, the scanning electron microscope images of the brittle sections of the CS / PPDO hydrogels prepared in other examples also show the same microstructural characteristics.
[0114] (ii) Mechanical strength test of chitosan / polydioxanone hydrogel;
[0115] The chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 and the CS hydrogel prepared in Comparative Example 1 were subjected to tensile tests. The specific test method is: a 35 mm × 20 mm × 2 mm (length × width × height) strip of gel is fixed at both ends of the instrument, and then the tensile strain and tensile strength of the hydrogel are calculated at a tensile speed of 200 mm / min; the specific test results are shown in Table 1 below.
[0116] Table 1:
[0117]
[0118]
[0119] It can be seen from the test results in Table 1 that compared with the pure CS hydrogel prepared in Comparative Example 1, the tensile strain at break and the tensile strength at break of the chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 are significantly improved. Specifically, the tensile strain at break is increased from 7% to 57%, and the tensile strength at break is increased from 170 KPa to 563 KPa.
[0120] In Example 1, Example 3, Example 5, Example 6 and Example 7, while keeping other conditions unchanged, as the amount of polydioxanone added to chitosan gradually increased, the tensile strain at break and the tensile strength at break of the chitosan / polydioxanone hydrogel showed a trend of first increasing and then decreasing; therefore, in modifying the network structure of the chitosan hydrogel using polydioxanone, the amount of polydioxanone added is also an important modification factor.
[0121] In the present application, the suitable range of the addition amount of polydioxanone relative to chitosan is 1wt% to 18wt%. When the addition amount of polydioxanone relative to chitosan is 1wt%, it can be seen from Table 1 that the tensile strain at break and the tensile strength at break decrease more significantly than the case where the addition amount is 3.5%. According to the actual experimental situation, when the addition amount of polydioxanone relative to chitosan is less than 1wt%, the tensile strain at break and the tensile strength at break of the hydrogel are not significantly improved. When the addition amount of polydioxanone relative to chitosan exceeds 18wt%, it is difficult for polydioxanone to be dispersed in the chitosan solution in the form of a solution, which also causes no significant improvement in the tensile strain at break and the tensile strength at break of the hydrogel.
[0122] Among them, when the addition amount of polydioxanone relative to chitosan is in the range of 3.5wt% to 12%, the tensile strength at break of the chitosan / polydioxanone hydrogel is greater than 400KPa, and the tensile strain at break is greater than 400KPa, which is consistent with the requirement for tensile strength at break of the hydrogel used as a tissue engineering scaffold; and when the addition amount of polydioxanone relative to chitosan is less than 3.5wt% or greater than 12%, at least one of the tensile strain at break and the tensile strength at break will significantly decrease; therefore, the suitable range of the addition amount of polydioxanone relative to chitosan is 1wt% to 18wt%, more preferably 3.5wt% to 12wt%.
[0123] like Figure 4 The graphs are the test results of mechanical tensile properties of CS / PPDO hydrogels prepared in Example 1, Example 3, Example 6 and Example 7, and CS hydrogel prepared in Comparative Example 1; it can be seen from the figure that the mechanical properties of the hydrogel prepared after the addition of PPDO are better than those of pure chitosan hydrogel. At the same time, the above data and diagrams show that the mechanical properties of the composite hydrogel gradually increase with the addition of polydioxanone. When the addition amount reaches 5wt%, the mechanical properties are the best, and then gradually decrease. The reason is probably that the addition of macromolecular polydioxanone forms an interpenetrating network in the hydrogel, which increases the mechanical properties of the hydrogel. However, excessive macromolecules will destroy the internal three-dimensional structure of the hydrogel, resulting in a decrease in mechanical properties. In summary, the mechanical properties of the hydrogel are best when the addition amount of polydioxanone is 5wt%.
[0124] However, the tensile strain at break and tensile strength at break of the chitosan / polydioxanone hydrogel prepared in Comparative Example 2 are too low because the deacetylation degree of chitosan is too low, which leads to a decrease in the solubility of chitosan and the corresponding decrease in crystallinity and moldability, resulting in too low mechanical properties.
[0125] The PPDO / CS hydrogels prepared in Examples 1 to 7 and the chitosan hydrogel in Comparative Example 1 were subjected to compression tests. The specific test method is as follows: a cylindrical hydrogel of 22 mm × 17 mm (diameter × height) is placed in a test instrument, and the gel column sample is compressed at a compression speed of 1 mm / s at room temperature, and the compression deformation is set to 30%. The specific test results are shown in Table 2 below.
[0126] Table 2:
[0127]
[0128]
[0129] It can be seen from the test results in Table 2 that compared with the pure CS hydrogel prepared in Comparative Example 1, the compressive strength and compressive yield strain of the chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 are significantly improved. Specifically, the compressive strength is increased from 70 KPa to 110 KPa, and the compressive yield strain is increased from 9.25% to 25.51%.
[0130] In Example 1, Example 3, Example 5, Example 6 and Example 7, while keeping other conditions unchanged, as the amount of polydioxanone added to chitosan gradually increased, the tensile strain at break and the tensile strength at break of the chitosan / polydioxanone hydrogel showed a trend of first increasing and then decreasing; therefore, in modifying the network structure of the chitosan hydrogel using polydioxanone, the amount of polydioxanone added is also an important modification factor.
[0131] However, the low deacetylation degree chitosan hydrogel prepared in Comparative Example 2 has too low mechanical strength and poor processing performance after modification with polydioxanone. Its mechanical properties can no longer meet the material requirements. Therefore, a series of subsequent tests such as compression were not carried out, and only other properties of chitosan with a deacetylation degree ≥ 95% were explored.
[0132] With the increase of the amount of polydioxanone added, the compressive strength of chitosan / polydioxanone hydrogel shows a trend of first increasing and then decreasing. The reason is that the appropriate amount of polydioxanone and chitosan form a cross-linked network to improve the compressive strength of the hydrogel. The presence of too much polydioxanone destroys the cross-linked network structure and the compressive performance decreases. The increase in compressive strength is beneficial to its application in tissue engineering.
[0133] The above two mechanical property test results prove that: the present application uses polydioxanone as a reinforcing material to structurally modify chitosan. By dispersing polydioxanone in a chitosan hydrogel containing a cross-linking agent and using a physical freeze-thaw method, a network interpenetrating structure is formed between the polydioxanone molecular chain and the chitosan hydrogel with a network structure, thereby achieving the purpose of significantly improving the tensile and compressive properties of the hydrogel.
[0134] (iii) Swelling rate test of chitosan / polydioxanone hydrogel;
[0135] The chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 and the CS hydrogel prepared in Comparative Example 1 were tested for swelling performance. The specific test method is: measuring the mass m1 of the hydrogel in the dry weight state, and then putting it into deionized water to fully absorb water and swell to record the mass m2, and the swelling rate R = (m2-m1) / m1; the specific test results are shown in Table 3 below.
[0136] Table 3:
[0137] name Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative Example 1 Swelling rate 629% 561% 552% 540.2% 532% 523% 505% 705%
[0138] It can be seen from the test results in Table 3 that, compared with the pure CS hydrogel prepared in Comparative Example 1, the swelling rate of the chitosan / polydioxanone hydrogel prepared in Examples 1 to 7 is reduced, but specifically, the swelling rate of the chitosan / polydioxanone hydrogel can still be stably maintained at more than 500%, still having a good swelling state, and the swelling rate of the chitosan / polydioxanone hydrogel hardly changes with the addition amount of polydioxanone.
[0139] like Figure 5 The figure shows the swelling rate curves of the chitosan / polydioxanone hydrogels prepared in Examples 3, 6 and 7 and the chitosan hydrogel prepared in Comparative Example 1 in water; it can be seen from the figure that, compared with the pure CS hydrogel, the water absorption rates of the three chitosan / polydioxanone hydrogels are lower, but the water absorption rates are stable at more than 550%, and they still have good swelling properties.
[0140] (IV) Degradation performance test:
[0141] The chitosan / polydioxanone hydrogels prepared in Examples 1 to 7 and the CS hydrogel prepared in Comparative Example 1 were subjected to a seven-week degradation experiment, specifically a simulated in vitro degradation experiment in a phosphate buffer with an initial pH of 7.4 in a constant temperature water bath at 37°C. The specific experimental results are shown in Table 4 below.
[0142] Table 4:
[0143] name Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative Example 1 Degradation 20.47% 21.36% 22.5% 23.1% 23.4% 24.1% 24.3% 19.54%
[0144] From the test results in Table 4, it can be seen that the chitosan hydrogel of Comparative Example 1 is well known. Although it has the advantages of good biocompatibility and in vivo degradability, the chitosan molecules have strong hydrogen bonds, which makes it only soluble in acidic media and has low solubility in water. The degradation performance of the chitosan / polydioxanone hydrogel prepared by Examples 1 to 7 is 20.47% to 24.3% after seven weeks of degradation, which is significantly improved compared with the chitosan hydrogel of Comparative Example 1. That is, after the chitosan / polydioxanone hydrogel of the present application is structurally modified, the degradation cycle is shortened, making it more suitable for human application environment requirements.
[0145] like Figure 6 The graphs are the mass loss changes during the degradation experiment of Example 3 and Comparative Example 1. It can be seen from the figure that the degradation rate of Example 3 is significantly faster than that of the comparative example in the first two weeks of the experiment. The reason is that the degradation cycle of polydioxanone is shorter than that of chitosan, so most of the polydioxanone begins to degrade in the first two weeks, and since the degradation cycle of chitosan itself is longer, it degrades slowly during the whole process, which also leads to the degradation rate of the overall composite hydrogel being greater than that of the chitosan hydrogel in the comparative example.
[0146] The degradation experiment proves that the chitosan / polydioxanone hydrogel of the present application optimizes the degradation rate of the chitosan hydrogel by structurally modifying the chitosan hydrogel, making it more suitable for use as a tissue engineering scaffold.
Claims
1. A chitosan / polydioxanone composite hydrogel, characterized in that: It is composed of chitosan with a deacetylation degree of ≥95% and a viscosity-average molecular weight of 1×10 4 ~1×10 6 The cross-linked polymer swelling liquid formed by polydioxanone is prepared by repeated freeze-thaw treatment; wherein the amount of polydioxanone is 1wt% to 18wt% of the weight of chitosan.
2. A method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: Here are the steps: S1, dissolving chitosan in an acidic aqueous solution to prepare a chitosan solution; S2, dissolving the cross-linking agent in the chitosan solution to obtain a chitosan solution containing the cross-linking agent; S3, dissolving polydioxanone in an organic solvent to prepare a PPDO solution; S4. Slowly add the PPDO solution to the chitosan solution containing the crosslinking agent, and keep it at a constant temperature of 55°C to 60°C and stir for 1 hour to mix the two evenly; continue stirring for 3 hours to 6 hours to allow the chitosan to fully hydrate and swell; then cool to room temperature to obtain a CS / PPDO swelling solution; S5, repeatedly freeze-thaw the CS / PPDO swelling solution to obtain a freeze-thawed CS / PPDO hydrogel; S6. The freeze-thawed CS / PPDO hydrogel is freeze-dried and then placed in deionized water to fully absorb water and swell, thereby obtaining a CS / PPDO composite hydrogel with swelling equilibrium and free of organic solvent.
3. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S1, the acidic aqueous solution is an acetic acid aqueous solution, a formic acid aqueous solution, an oxalic acid aqueous solution or a carbonic acid aqueous solution with a pH of 3 to 6.
4. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S2, the cross-linking agent is sodium citrate, calcium chloride or glutaraldehyde, preferably sodium citrate; the amount of the cross-linking agent is preferably 0.25 to 0.3 times the weight of chitosan.
5. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S3, the organic solvent is dimethyl sulfoxide, N-dimethylformamide or chloroform.
6. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: Before performing step S5, the CS / PPDO swelling solution is defoamed at room temperature to obtain a uniform CS / PPDO swelling solution.
7. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S5, the method of repeated freeze-thaw treatment is: the CS / PPDO swelling solution is placed at -48°C to -12°C and frozen for 8h to 12h, and then returned to room temperature for 3h to 6h; the above freeze-thaw operation is repeated 4 to 6 times to obtain a frozen-thawed CS / PPDO hydrogel.
8. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S6, the freeze-drying treatment temperature is -60°C to -40°C, the pressure is 0.4 mbar to 0.01 mbar, and the freeze-drying time is 24h to 48h.
9. The method for preparing the chitosan / polydioxanone composite hydrogel according to claim 1, characterized in that: In step S6, the water absorption and swelling method is: placing the freeze-dried CS / PPDO hydrogel in deionized water to absorb and swell for 12 hours to 24 hours, so that the hydrogel fully absorbs water.
10. An application of the chitosan / polydioxanone composite hydrogel as claimed in claim 1, characterized in that: Used in skin tissue engineering, soft tissue engineering and bone tissue engineering.
Citation Information
Patent Citations
Preparation technology of polylactic acid anti-adhesion gel
CN112451749A
Poly (p-dioxanone) / polyvinyl alcohol hydrogel and preparation method thereof
CN115895155A
High-strength hydrogel / superfine fiber non-woven composite material as well as preparation method and application thereof
CN119061583A
Fabrication method of hybrid hydrogel, Fabricaltion method of injection comprising the same, and Hybrid hydrogel
KR102094407B1
Gel suitable for implantation and delivery system
US20050186240A1
Cited By
Fully degradable twin-spun non-woven flexible composite material and preparation method and application thereof
CN120250243A